Damage characterization of reinforced concrete beams under different failure modes using acoustic emission. (April 2021) - Prem, Prabhat Ranjan; Verma, Mohit; P.S.Ambily,
Abstract: Recently, a lot of studies have focused on the crack classification and damage characterization in concrete specimens combining acoustic emission (AE) monitoring with the mechanical testing. However, it is observed that very limited attention is given towards identification of failure mechanism (such as shear, shear-flexure and flexure) based on AE monitoring. This research gap is being addressed in the present study. Nine different under reinforced beams are designed to fail in shear, mixed and flexure modes. These beams are mechanically tested and the damage progression is monitored simultaneously using AE. The AE parameters (such as amplitude, energy, rise angle, average frequency, signal strength, amplitude, energy b-value, severity index, and historic index) thus obtained are correlated with the different failure modes. From the study, it is found that AE features are strongly related to the nature of failure in the RC beams. The results of this study demonstrates the effectiveness of the AE technique for monitoring cracks and damage characterization in RC beams. The work presented in this study will aid the formulation of appropriate retrofitting strategy for the life enhancement of critical infrastructure.